2011
DOI: 10.1080/10937404.2011.556048
|View full text |Cite
|
Sign up to set email alerts
|

Nonpulmonary Outcomes of Asbestos Exposure

Abstract: The adverse pulmonary effects of asbestos are well accepted in scientific circles. However, the extrapulmonary consequences of asbestos exposure are not as clearly defined. In this review the potential for asbestos to produce diseases of the peritoneum, immune, gastrointestinal (GIT), and reproductive systems are explored as evidenced in published, peer-reviewed literature. Several hundred epidemiological, in vivo, and in vitro publications analyzing the extrapulmonary effects of asbestos were used as sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 220 publications
(368 reference statements)
0
47
0
1
Order By: Relevance
“…Consequently, small-size fibers should not be excluded from those contributing to the induction of human MM, especially in high exposure environments. This is further supported by the fact that ultrafine fibers are particularly suitable for penetration from the proximal area to the peripheral part of the lung and migration from the lung to the pleura and the other sites within the human [6,77,78]. Therefore, it is difficult to exclude fibers of a particular dimension from those producing disease within the lung or extrapulmonary sites.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, small-size fibers should not be excluded from those contributing to the induction of human MM, especially in high exposure environments. This is further supported by the fact that ultrafine fibers are particularly suitable for penetration from the proximal area to the peripheral part of the lung and migration from the lung to the pleura and the other sites within the human [6,77,78]. Therefore, it is difficult to exclude fibers of a particular dimension from those producing disease within the lung or extrapulmonary sites.…”
Section: Discussionmentioning
confidence: 99%
“…Although some investigators have considered these as adjuvant effects, silica can influence circulating immunocompetent cells, particularly T reg and T resp cells. Correlations between asbestos exposure and autoimmune disease also suggest a higher-than-expected risk of systemic autoimmune disease among asbestos-exposed populations (Bunderson-Schelvan et al, 2011), although in general this association is less compelling than that found with silica. An animal model has been developed for asbestos-induced autoimmune disease, which is significant since the method employs normal rather than genetically prone mice (Pfau et al, 2008).…”
Section: Environmental-induced Autoimmunitymentioning
confidence: 95%
“…Inhaled asbestos fibers are partly transported out of the lungs by mucociliary clearance and subsequently swallowed [2]. In addition, an inadvertent, direct ingestion of asbestos fibers is possible [8]. In vitro and in vivo studies showed that asbestos fibers penetrated and interacted not only with the mucosal cells of the pulmonary system but also with the mucosal cells of the gastrointestinal tract [27].…”
Section: Mortality Due To Gastrointestinal Malignanciesmentioning
confidence: 99%
“…In vitro and in vivo studies showed that asbestos fibers penetrated and interacted not only with the mucosal cells of the pulmonary system but also with the mucosal cells of the gastrointestinal tract [27]. However, evidence regarding the carcinogenic potency of asbestos in the gastrointestinal tract as well as evidence regarding increased mortality from gastrointestinal malignancies in asbestos exposed subjects is limited and inconsistent [8]. Associations of occupational exposure to asbestos with increased mortality risk due to esophageal cancer [28], cancer of the small intestine [28] or cancer of the large intestine [29] have only been detected in single cohort studies.…”
Section: Mortality Due To Gastrointestinal Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation